Empowering The Kemang Bogor Batik Association Through A Batik Waste Processing Installation, Cooperatives, And Digital Marketing - Sutanto; Eneng Tita Tosida; Fredi Andria (Research Collaboration Community (Rescollacom), 2026)
The Kemang Batik Association in Bogor Regency is a community-based creative industry with significant cultural and economic potential, however, its sustainability is constrained by untreated batik wastewater, weak financial management, and limited marketing capacity. Batik production activities generate colored liquid waste that is often discharged directly into the environment, posing pollution risks. In addition, the absence of formal cooperative institutions and reliance on conventional marketing methods hinder business growth and income stability among artisans. This community service program aimed to empower the Kemang Batik Association through an integrated approach encompassing environmentally friendly technology, institutional strengthening, and digital marketing. A portable electrocoagulation-based wastewater treatment installation (IPAL) namely Hydrobex, with a capacity of 100 liters per day was implemented to reduce pollutant loads in batik effluent. Furthermore, a Batik Cooperative was established to improve financial governance, collective management, and access to capital. Digital marketing platforms utilizing social media, online marketplaces and batik game based marketing (GARLaTik) were developed to expand market reach and enhance product visibility. The program was conducted through participatory training, technology transfer, mentoring, and continuous evaluation involving academics, students, and community members. The results indicate improved environmental awareness, strengthened organizational capacity, and increased adoption of digital marketing practices. This integrated empowerment model supports sustainable community development, promotes a green economy, and contributes to the achievement of relevant Sustainable Development Goals.